Carbon Pools and Associated Soil Enzymatic Activities as Influenced by Long-term Application of Fertilizers and Manure in Lowland Rice Soil - and P. Bhattacharyya, D. Srinivas, M. Bharatha Lakshmi (Journal of the Indian Society of Soil Science, 2015)
The effect of long-term (21 years) fertilizer application on soil carbon pools, its functional groups in humic acids and associated soil enzymatic activities was investigated in tropical flooded rice. The five treatments were non-fertilized control, nitrogen (N) (90 kg ha-1), farmyard manure (FYM) (10 t ha-1), NPK (90:45:45 kg ha-1:: N:P2O5:K2O) and FYM+NPK. On average, the microbial biomass carbon (MBC) content was significantly higher in FYM+NPK treatment as compared to control (by 30%), 100% N, 100% NPK + FYM treatments. The enzyme activities, viz. dehydrogenase, b-glucosidase, acid and alkaline phosphatase were found significantly higher under FYM + NPK treated plots compared with control by 107, 170, 133 and 190 per cent, respectively. The characteristic humic acid spectra revealed that FYM and NPK treated plot contains aromatic functional C groups, which have the potential to sequester C in the long run. Therefore, the combined application of FYM + NPK is a viable option for managing soil fertility as well as sustaining rice yield (4.1-5.7 t ha-1) in tropical flooded soils. The study is novel in the sense it describes soil carbon pools including labile active and passive pools in relation to soil functional microbial diversity under lowland flooded rice.